2020
DOI: 10.1002/pc.25725
|View full text |Cite
|
Sign up to set email alerts
|

Sandwiched polyimide‐composite separator for lithium‐ion batteries via electrospinning and electrospraying

Abstract: A novel type of sandwiched separator for lithium-ion batteries has been developed by combining electrospinning and electrospraying techniques. This separator consists of three layers in which the top and bottom layers are prepared by electrospinning a poly(amic acid) ammonium salt (PAAS) solution and the middle layer is obtained by electrospraying a mixture of the PAAS solution and inorganic nanoparticles (SiO 2 or Al 2 O 3). Subsequently, the sandwiched separators are imidized at 250 C in a nitrogen atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…They had achieved this by the fabrication of hybrid nanofibers with inorganic nanoparticles sandwiched between two layers. Here, immobilization of nanoparticles on the surface of a nanofiber was performed by electrospraying [ 152 ]. Additionally, hybrid nanofibers contained a layer of SiO 2 and Al 2 O 3 .…”
Section: Fabrication Of Inorganic Nps Functionalized Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…They had achieved this by the fabrication of hybrid nanofibers with inorganic nanoparticles sandwiched between two layers. Here, immobilization of nanoparticles on the surface of a nanofiber was performed by electrospraying [ 152 ]. Additionally, hybrid nanofibers contained a layer of SiO 2 and Al 2 O 3 .…”
Section: Fabrication Of Inorganic Nps Functionalized Nanofibersmentioning
confidence: 99%
“…Interestingly, we have observed that 3D PCL microfibers prepared by centrifugal spinning showed a better proliferation of fibroblasts while 2D core/shell nanofibers prepared by needleless emulsion electrospinning showed a higher proliferation of keratinocytes [ 169 ]. Polycaprolactone/gelatin/hyaluronic acid nanofibers were developed to mimic a glioblastoma tumor extracellular matrix [ 152 ]. In another study, electrospun PCL membranes blended with hydroxyapatite (HA) were developed, and its potential in differentiating inflamed dental pulp stem/progenitor cells (IDPSCs) into odontoblasts was evaluated [ 180 ].…”
Section: Potential Applications Of Hybrid Multifunctional Nanofibersmentioning
confidence: 99%
“…The future trends on the separator technology include the development of more complex and multifunctional membranes, particularly with the increasing of the devices' safety, by adding shutdown functions to the separators [199]. Novel separator architectures based on three layers were developed combining electrospinning and electrospraying techniques and composed of PI and poly(amic acid) ammonium salt (PAAS) solution with inorganic nanoparticles (SiO 2 or Al 2 O 3 ) [185]. Another three-layer separator was produced based on poly (ethylene-co-vinyl acetate) (EVA)/polyimide (PI)/EVA (PIE) with high thermal stability and a shutdown function [230].…”
Section: Separator Membranementioning
confidence: 99%
“…[11][12][13] Electrospinning is another technique that seems appropriate for developing flexible devices although it has not been explored deeply with respect to the fabrication of temperature sensors. [14] It is simple, productive and compared to solvent cast films, electrospun films show higher malleability due to a very high aspect ratio. [10,15] Wang et al prepared an Ag-SBS-based bi-modal electrospun flexible temperature-pressure sensor with linear temperature sensitivity and stable temperature observations under various pressure loadings.…”
Section: Introductionmentioning
confidence: 99%